Outcomes of subintimal plaque modification in chronic total occlusion percutaneous coronary intervention. Issue 5 (4th December 2019) - Xenogiannis, Iosif; Choi, James W.; Alaswad, Khaldoon; Khatri, Jaikirshan J.; Doing, Anthony H.; Dattilo, Phil; Jaffer, Farouc A.; Uretsky, Barry; Krestyaninov, Oleg; Khelimskii, Dmitrii; Patel, Mitul; Mahmud, Ehtisham; et al.
Abstract: Background: When crossing into the distal true lumen fails during chronic total occlusion (CTO) percutaneous coronary intervention (PCI), subintimal plaque modification (SPM) is often performed to restore antegrade flow and facilitate subsequent lesion recanalization. Methods: Between January 2012 and May 4, 2019, 4, 659 CTO PCIs were included in the PROGRESS‐CTO registry, of which 935 (20%) had a prior unsuccessful attempt. Of those 935 patients, 119 (13%) had prior SPM. We analyzed the outcomes of the 58 SPM procedures for which data were available, as well as the outcomes of the 60 subsequent CTO PCI attempts. Results: Mean patient age was 67 ± 9 years and 86% were men. Patients had high prevalence of cardiovascular risk factors such as dyslipidemia (91%), hypertension (93%) diabetes (48%), prior PCI (61%), and prior coronary artery bypass graft surgery (47%). The target CTO lesions often had proximal cap ambiguity (54%), moderate/severe calcification (73%), moderate/severe tortuosity (63%), and high J‐CTO score (mean 3.2 ± 1.1). The technical and procedural success of subsequent CTO PCI were high (83% for both) with an acceptable rate of in‐hospital major adverse cardiovascular events (3.3%). Technical and procedural success were higher for repeat attempts that were performed ≥60 days after the index CTO PCI (94% vs. 69%, p = .015). Median (interquartile range) subsequent procedure time was 147 (100, 215) min, contrast volume was 185 (150, 260) ml, and air kerma radiation dose was 2.5 (1.4, 4.2) Gray. Conclusion: Repeat CTO PCI attempts after SPM are associated with high likelihood for successful revascularization with acceptable risks.